2000
DOI: 10.1152/jn.2000.83.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Corticomotoneuronal (CM) Cell Postspike Effects and Cell-Target Muscle Covariation

Abstract: The presence of postspike facilitation (PSpF) in spike-triggered averages of electromyographic (EMG) activity provides a useful means of identifying cortical neurons with excitatory synaptic linkages to motoneurons. Similarly the presence of postspike suppression (PSpS) suggests the presence of underlying inhibitory synaptic linkages. The question we have addressed in this study concerns the extent to which the presence and strength of PSpF and PSpS from corticomotoneuronal (CM) cells correlates with the magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Others have examined the correlation or coherence between EMG signals and either the discharge of single neurons (Holdefer and Miller 2002;McKiernan et al 2000;Schwartz and Adams 1995), local field potentials (Baker et al 1999), or electroencephalographic signals (Halliday et al 1998;Mima et al 2000). However, to the best of our knowledge, there has been only one other study that attempted to account for the time course of EMG modulation on the basis of the discharge of multiple neurons (Fetz et al 1989).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Others have examined the correlation or coherence between EMG signals and either the discharge of single neurons (Holdefer and Miller 2002;McKiernan et al 2000;Schwartz and Adams 1995), local field potentials (Baker et al 1999), or electroencephalographic signals (Halliday et al 1998;Mima et al 2000). However, to the best of our knowledge, there has been only one other study that attempted to account for the time course of EMG modulation on the basis of the discharge of multiple neurons (Fetz et al 1989).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Additionally, lag-dependent correlations may occur through indirect effects. For example, this effect could emerge if a given cortical motoneuron does not innervate the muscle being recorded, but instead innervates a different muscle that acts in synchrony with the former muscle (McKiernan et al 2000). It is also possible that some of the lag-dependent correlations observed in our study reflected the cortical unit's responses to proprioceptive feedback generated by muscle contractions.…”
Section: Discussionmentioning
confidence: 88%
“…Several previous studies came to similar conclusions. McKiernan et al (2000) reported only a weak relationship between short-latency postspike effects (i.e., a relatively stable relationship based on direct connectivity) and more broad neuron-muscle covariations. Another study (Schwartz and Adams 1995) reported time-dependent changes in cortico-EMG cross-correlation during a sinusoidal tracking task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations